A Practitioner's Handbook for Eco-Industrial Parks : Implementing the International EIP Framework - United Nations Industrial Development Organization; World Bank Group; Deutsche Gesellschaft für Internationale Zusammenarbeit; Ministry of Trade, Industry and Energy of the Republic of Korea (World Bank, Washington, DC, 2018)
The EIP Practitioner’s Handbook [or “the Handbook”] is a practical, step-by-step guide that takes stakeholders through the entire process of operationalizing the International EIP Framework. It addresses a wide range of practitioners including industrial park operators; firms located in industrial parks; industrial park planners and developers; decision makers; governmental officials and regulators at the central, provincial and local levels; financing bodies; and funding agencies, donor and international development institutions supporting client governments in designing policy frameworks and facilitating the promotion of EIPs. The Handbook is intended to help practitioners operationalize the International EIP Framework at the national and /or park level, as well as specific EIP performance requirements set in the Framework.